Enhancing quality of life in diabetes mellitus patients through rational emotive behavior therapy: A randomized controlled trial - Rosdiana, Rosdiana; Shofiyah, Shofiyah; Karosekali, Ester; Sovitriana, Rilla; Alsa, Asmadi (Edelweiss Applied Science and Technology, 2025)
Diabetes Mellitus, a chronic metabolic disease, is linked with psychological suffering alongside a surplus of distress, as well as reduced quality of life (QoL), which in turn self-perpetuates a diabolical interaction between life and these two elements. However, diabetes disorder remains highly understudied, especially in the application of psychologically-based non-pharmacological programs such as Rational Emotive Behavior Therapy (REBT). This randomized pretest-posttest controlled trial was conducted to assess the period effect of REBT on improving QoL in 10 patients from UPT Klinik Kesehatan Universitas Sriwijaya, Indonesia. Participants were divided into two groups: experimental (n=5), who received 10 weekly treatment sessions of REBT focusing on cognitive restructuring and emotional regulation, and a control group (n=5) who continued to receive standard care. QoL was assessed with the Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ; Cronbach’s α=0.82) validated for use in Indonesia. The Wilcoxon Signed-Rank Test showed that statistically significant improvement in QoL occurred in the experimental group (p=0.005). In the reframed group, average scores improved from 43 (low QoL) to 60 (high QoL), while the control group placidly varied from 47 to 49, thus showcasing their negligible change. Anxiety was effectively reduced; emotional resilience and adaptive coping were effectively promoted by REBT. Those outcomes justify the need for REBT as part of interdisciplinary diabetes care, as well as any other integrated therapy to launch a wider scale trial with larger populations and longitudinal studies to claim real benefits for patients with diabetes mellitus.